Implementasi Agen Perubahan Dalam Menanggulagi Kasus Bullying Di Lingkungan Sekolah - Ilham Hidayat; Hajar Sailirrohmah; Munib Amalia Khasanah; Salsabilla Septiana Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to describe the implementation of Change Agents in Addressing Bullying Cases in School Environments. Child violence, especially in the form of bullying, is a serious issue that is increasingly worrying in Indonesia. verbal. Schools are one of the environments that are vulnerable to bullying. The formation of change agents in schools is one of the efforts to prevent bullying. Change agents are students who are selected from among the students in the school, who are considered to have the most interaction with other students. Change agents have preventive and curative roles in preventing bullying. This study was conducted in a descriptive form using a qualitative approach. A qualitative approach is a research method based on postpositivism philosophy. The results of the study showed that Change agents in schools play a preventive and curative role in preventing bullying. The preventive role involves the formation of change agents and monitoring of bullying cases, while the curative role involves reporting and processing bullying cases to the guidance counselor and cooperation with the parents of the victim and the perpetrator.